2019
DOI: 10.1111/ijcp.13341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of heart failure with mid‐range and preserved ejection fraction in octogenarians: Results of a multicentre, observational study

Abstract: Summary Objectives To compare real‐world characteristics and management of individuals aged 80 and older with heart failure (HF) and mid‐range ejection fraction (HFmrEF) and heart failure with preserved ejection fraction (HFpEF) derived from a large cohort of survey and to compare them with those younger than 80 from the same survey. Methods This is an observational, multicentre and cross‐sectional study conducted in Turkey (NCT03026114). Consecutive 1065 (mean age of 67.1 ± 10.6 years) patients admitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In a study analyzing long-term mortality after coronary artery bypass grafting, octogenarians showed a mortality rate of 23% 5 years post-surgery [18], and a 5 year mortality rate of 44% has been reported in octogenarians undergoing surgical aortic valve replacement [19], which is lower than the mortality seen in our cohort of HF patients. A sex difference in prognosis was also observed in octogenarian HF patients, similar to that which has also been observed in European patients [20]. Sarcopenia, which is closely related with frailty, was found to be more prevalent in the elderly, and was an independent predictor of mortality.…”
Section: Distinctions Of Octogenarian Hf Patientssupporting
confidence: 81%
“…In a study analyzing long-term mortality after coronary artery bypass grafting, octogenarians showed a mortality rate of 23% 5 years post-surgery [18], and a 5 year mortality rate of 44% has been reported in octogenarians undergoing surgical aortic valve replacement [19], which is lower than the mortality seen in our cohort of HF patients. A sex difference in prognosis was also observed in octogenarian HF patients, similar to that which has also been observed in European patients [20]. Sarcopenia, which is closely related with frailty, was found to be more prevalent in the elderly, and was an independent predictor of mortality.…”
Section: Distinctions Of Octogenarian Hf Patientssupporting
confidence: 81%
“…Considering that the majority of our patients are in NYHA Class II, it can be asserted that they follow an adequate treatment regimen as established in the current clinical practice guidelines [ 36 ]. The degree of dyspnea, when considering gender, showed that women with HF are more limited in this regard, presenting a higher percentage of individuals in NYHA classes III and IV, as current the literature has shown [ 32 , 37 , 38 ]. This could explain why women participating in this study present worse results in the Barthel index.…”
Section: Discussionmentioning
confidence: 90%
“…Hormonal, pathophysiological, and structural factors have been postulated as explanations for these gender differences, but much remains to be investigated [ 30 , 31 ]. We also know that HFpEF is higher in older age groups [ 32 , 33 ], which justifies the lower number of people with HFrEF among the studied population. Research is nowadays scarce, mainly due to the smaller number of women and older people included in clinical trials [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 97%
“…These results reveal the need of adding the assessment of SAR in routine echocardiographic evaluation of HF patients. The HFPEF is currently the most common form of HF, mainly because of the accelerated aging and high prevalence of comorbidities [14]. Identifying high and low-risk ambulatory patients with HFpEF can improve care by preventing delays in appropriate treatment for high-risk patients.…”
Section: Discussionmentioning
confidence: 99%